2016
DOI: 10.1186/s40880-016-0163-6
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine improves survival in patients with recurrent or metastatic nasopharyngeal carcinoma

Abstract: For decades, the selection of chemotherapeutic regimens for the treatment of recurrent or metastatic nasopharyngeal carcinoma has been mainly empirical. To our knowledge, there is no phase 3 trial that has been conducted to determine the optimal treatment for these patients before our publication. Recently, we published an article in The Lancet entitled “Gemcitabine plus cisplatin versus fluorouracil plus cisplatin in recurrent or metastatic nasopharyngeal carcinoma: a multicentre, randomised, open-label, phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The GEM20110714 trial was the first randomized, phase III trial of palliative chemotherapy in RM-NPC. 4 , 5 This trial compared the efficacy and safety of gemcitabine plus cisplatin (GP) with that of fluorouracil plus cisplatin (FP) in first-line treatment of RM-NPC.…”
Section: Introductionmentioning
confidence: 99%
“…The GEM20110714 trial was the first randomized, phase III trial of palliative chemotherapy in RM-NPC. 4 , 5 This trial compared the efficacy and safety of gemcitabine plus cisplatin (GP) with that of fluorouracil plus cisplatin (FP) in first-line treatment of RM-NPC.…”
Section: Introductionmentioning
confidence: 99%
“…The majority (223/266, 83.8%) of toxicities and adverse events was judged on Grades1/2. About one-third of patients with NPC suffer of distant metastases and resultant treatment failure [15]. Liver metastasis is the second common metastasis site, which accounts for 30% of such cases, following bone metastasis (70%) and followed by lung metastasis (18%) [16], but has the worst prognosis (with reported mOS of 3-5 months) [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary result of phase 2 trial with tislelizumab (an anti-PD-1) which was presented in ASCO 2019 meeting showed 43% objective response rate and 10.4 months of progression-free survival (PFS) in those with advanced metastatic or recurrent nasopharyngeal cancer. This was shown to confer longer PFS compared to historical control (PFS of 7 months) with second-line chemotherapy [41]. However, the survival benefit is yet to be proven in phase 3 study.…”
Section: Current Work In Progress For Potential Immune-related Targementioning
confidence: 99%